(untitled) (Philology, 2026)
The main point of departure for the present paper is de Beaugrande and Dressler’s claim that every text evokes the creation of a textual world which is constructed mentally and signaled linguistically. The paper synchronizes that conviction with Werth’s claim of the existence of another type of ‘world’ – ‘discourse world’. In tackling the issue of how the two types of worlds (co-)exist, the paper relies theoretically on the cognitive principle of profiling. The investigation presented here focuses on one specific kind of linguistic evidence of the operation of text and discourse worlds – on audience addresses used in political speeches. The paper reports and discusses the results from a study involving 20 respondents. The study verifies the hypothesis of a heightened communicative effect through evoking discourse worlds through direct audience addresses.